2021
DOI: 10.3389/fendo.2021.749451
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in Sex Hormone-Induced Disorder of Energy Metabolism in Males and Females

Abstract: Androgens have a complex role in the regulation of insulin sensitivity in the pathogenesis of type 2 diabetes. In male subjects, a reduction in androgens increases the risk for insulin resistance, which is improved by androgen injections. However, in female subjects with polycystic ovary syndrome (PCOS), androgen excess becomes a risk factor for insulin resistance. The exact mechanism underlying the complex activities of androgens remains unknown. In this review, a hormone synergy-based view is proposed for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 161 publications
0
7
0
2
Order By: Relevance
“…More importantly, PCOS patients with IR exhibited signi cantly lower mitochondrial copy numbers, suggesting that mitochondrial dysfunction may be associated with IR symptoms in PCOS patients [49][50]. Overactivated mitochondria produce excess reactive oxygen species (ROS), which exacerbate oxidative stress [51], leading to IR in the skeletal muscle and liver [52]. In the current study, acupuncture treatment was effective in improving mitochondrial dysfunction in PCOS patients.…”
Section: Discussionmentioning
confidence: 68%
“…More importantly, PCOS patients with IR exhibited signi cantly lower mitochondrial copy numbers, suggesting that mitochondrial dysfunction may be associated with IR symptoms in PCOS patients [49][50]. Overactivated mitochondria produce excess reactive oxygen species (ROS), which exacerbate oxidative stress [51], leading to IR in the skeletal muscle and liver [52]. In the current study, acupuncture treatment was effective in improving mitochondrial dysfunction in PCOS patients.…”
Section: Discussionmentioning
confidence: 68%
“…The primary objective was to examine the influence of NA supplementation on capillary regression, emphasizing its effects on mitochondrial biogenesis and the expression of PGC-1α. It is acknowledged that both testosterone and estrogen can influence the mitochondrial pathway through PGC-1α (Yin et al, 2021). Additionally, Mortreux et al (2021) reported that following 14 days of hindlimb suspension, female rats exhibited more stable hormonal levels compared to their male counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, patients with PCOS with IR exhibited significantly lower mitochondrial copy numbers, suggesting that mitochondrial dysfunction may be associated with IR symptoms in patients with PCOS (Ding et al, 2017; Saeed et al, 2019). Overactivated mitochondria produce excess reactive oxygen species, which exacerbate oxidative stress (Zhang, Zhao, et al, 2019), leading to IR in the skeletal muscle and liver (Yin et al, 2021). In the current study, acupuncture treatment was effective in improving mitochondrial dysfunction in patients with PCOS.…”
Section: Discussionmentioning
confidence: 99%